Analisis Hukum Perjanjian Kredit di Bank Konvensional dalam Perspektif Perlindungan - Rafliyansyah; Rasji (Jurnal Hukum Lex Generalis, 2025)
Credit agreements in conventional banks play an important role in supporting economic development, but they pose challenges for legal protection for debtors due to the imbalance of rights and obligations in standard agreements. A juridical analysis of banking regulations and practices shows that although the principle of prudence and POJK No. 42/POJK.03/2017 have been implemented, the resolution of defaults still often occurs through litigation, which is less effective and does not optimally protect debtors. This research concludes the need for regulatory updates and non-litigation dispute resolution mechanisms to strengthen debtor legal protection.